THE EFFECT OF THE PROBLEM-BASED LEARNING MODEL ASSISTED BY QUESTION CARD MEDIA ON MATHEMATICS LEARNING OUTCOMES - Yasmin Maulidasari; Rais Hidayat; Rukmini Handayani (Universitas Nias Raya, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model supported by question card media on students' mathematics learning outcomes. The research employed a quasi-experimental design involving fourth-grade students at SD Negeri Margajaya 4, with a total sample of 48 students selected through purposive sampling. Data on students' learning outcomes were collected using pre-tests and post-tests. To analyze the data, several statistical tests were conducted, including the N-Gain test, normality test, and homogeneity test as prerequisites before performing the hypothesis test (t-test). The average N-Gain score in the experimental class was 70, while the control class scored 59. Hypothesis testing using the t-test showed that the calculated tvalue (3.32929) exceeded the critical tvalue (2.01290) at a 5% significance level. This result indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Based on these findings, it can be concluded that the implementation of the Problem-Based Learning model assisted by question card media has a significant positive effect on students’ mathematics learning outcomes. The integration of interactive media within a student-centered learning model enhances engagement and improves academic achievement in mathematics.